Twice Exceptional in Early Childhood - Qur'ani, Rizdayanti; Syafril, Syafrimen (International Journal of Multidisciplinary Research of Higher Education, 2025)
Twice exceptional children are individuals who have a combination of exceptional talent and learning disorders, such as Attention Deficit Hyperactivity Disorder, dyslexia or autism, which pose unique challenges in education. This research aims to analyze the internal and external factors that influence the development of twice exceptional children. Internal factors such as cognitive imbalance and low self-perception often hinder their achievement, while external factors such as lack of educational support and early identification exacerbate the situation. This study utilized the Systematic Literature Review method which involved searching literature from highly reputable sources such as Scopus, Springer, ERIC, ScienceDirect, and Google Scholar. A total of 25 documents obtained from Q1-Q4 and SINTA 2 journals were analyzed using NVivo 12 Pro software. The results showed that twice exceptional children often face major learning difficulties such as Attention Deficit Hyperactivity Disorder, dyslexia and autism that affect their academic performance. Internal factors found include cognitive imbalance, low self-esteem and anxiety, while external factors affecting their development include lack of early identification and lack of appropriate educational support. Effective educational approaches involve strength-based interventions, differentiated instruction and training for educators to address their needs holistically. The implications of this research suggest that education policy in Indonesia needs to be updated to create a system that is more inclusive and responsive to twice exceptional children. A multidimensional approach that incorporates cognitive, social and emotional aspects is needed to support the optimal development of twice exceptional children. In addition, training for educators and parental involvement are key factors to create a supportive environment for their development, both at school and in the community.